INVESTIGATION OF THE SOCIODEMOGRAPHIC PROPERTIES EFFECTING IN THE EXAMINATION OF ADOLESCENT - BAL, Fatih (Atlas Journal, 2018)
Exam anxiety, expressed as a bad emotion or excitement, is a significant problem with physiological, behavioral and cognitive elements in a formal examination or any procedure. Today’s exams play a major determinant role in the life of the adolescent individual and constitute a great anxiety and stress situation. In our study, it was examined whether the individuals who were prepared for the exams in the adolescence period were different according to the level of exam anxiety levels whether they were gender, class, family’s marital status, family income level or academic support.